Perspectives of being a female informal caregiver of children with disabilities - Carvalho, Isabella Joyce Silva de Almeida; França, Inácia Sátiro Xavier de; Sousa, Francisco Stélio de; Linhares, Francisca Márcia Pereira; Lira, Ana Luisa Brandão de Carvalho; Coura, Alexsandro Silva (Revista de Enfermagem da UFPI, 2023)
Objective: To know the perspective of being a female informal caregiver of children with disabilities. Methods: A descriptive, exploratory and qualitative study. The participants were female informal caregivers of children with disabilities. Data collection took place through four virtual focus groups, via the Google Meet platform. The analysis was carried out by means of Thematic Content Analysis. The criterion for categorization was semantic. The categories that emerged were named in the light of the relevant scientific literature. Results: Three categories emerged after analyzing the focus groups, namely: Category 1 - Peers as support network; Category 2 - The spirituality experience; and Category 3 - Concerns about social and legal aspects. Conclusion: The perspective of being a female informal caregiver of children with disabilities involves a negative and positive aspect. Negative, in the sense that there is dissatisfaction through the judgments imputed by society in relation to them and the legal framework that governs their rights. Positive, through the support network comprised by other mothers of children with disabilities and the spirituality experience in the care context, making the care routine smoother.